Synthesis, crystal structures and properties of new lanthanide benzene-1,2,3- triyltris(methylenephosphonates) - Bazaga-García, Montse; Salcedo, Inés R.; Pérez-Colodrero, Rosario Mercedes; Olivera-Pastor, Pascual; Zareba, Jan K.; Cabeza-Díaz, Aurelio (My University, 2025)
Metal phosphonates are usually water-containing acidic solids, in which the formation of extended H-bond networks is possible, making them suitable for their application as proton conductors. Additionally, these properties can be further enhanced by post-synthesis modifications, such as ammonia adsorption. In this study, we report the synthesis and structural characterization of a new series of isostructural compounds formed by combining the polyfunctional benzene-1,2,3- triyltris(methylene) phosphonic acid (BTTMP) with lanthanide ions. Under hydrothermal conditions, three series of isostructural compounds were obtained and their crystal structures solved ab initio, from X-ray powder diffraction data using laboratory and synchrotron radiation. All compounds exhibit layered structures with variable coordination modes. Apart from the structural characterization, we present preliminary results of their proton conductivity properties.
Keywords: Cristalografía; Metales de las tierras raras; Fotoluminiscencia; Lanthanide phosphonates; Coordination polymers; Proton conductivity; Crystal structure